Synthesis and anti-aging properties of vinyl triethoxysilane modified fluorinated acrylate polymer coatings for stone relics conservation - Ma, Chuang; Chin, Sim Yee (Pleiades Publishing, Ltd., 2025)
The degradation of stone cultural relics due to environmental factors, such as freeze-thaw, acid rain, and UV radiation, has necessitated the development of advanced protective coatings. In this study, fluorinated poly(methyl methacrylate-butyl acrylate) modified by vinyl triethoxysilane coating was synthesized via a one-pot method to enhance the durability and protective performance of coatings. The structure, thermal stability, and microstructure of the synthesized polymer were characterized using FTIR, XRD, TG, and SEM. The aging resistance of the coating formed was systematically evaluated under simulated freeze-thaw, acid, and UV aging conditions. Key properties, including hydrophobicity, chromaticity difference (ΔE), transparency, and mass loss rate, were analyzed before and after aging. Among the aging factors, UV exposure exhibited the most pronounced impact on these properties. However, polymer coatings with 18.5 mmol vinyl triethoxysilane demonstrated superior resistance to UV-induced degradation, maintaining a contact angle of 104.55°, the stability change of ΔE is 0.73, and acceptable transparency and mass loss rates after aging.